2008
DOI: 10.1136/ard.2008.096669
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for a first thrombotic event in antiphospholipid antibody carriers. A multicentre, retrospective follow-up study

Abstract: Hypertension or medium/high titres of IgG aCL are risk factors for a first thrombotic event in asymptomatic aPL carriers and primary prophylaxis is protective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 13 publications
6
66
0
2
Order By: Relevance
“…And as result of a multivariate analysis, hypertension appeared as a risk for arterial thrombosis (Table 5). Ruffatti et al reported hypertension as a risk for the first thrombotic event in aPL carriers by retrospective and prospective cohort studies 16,17 . Previous studies with smaller numbers of patients have also shown the association between hypertension and arterial thrombosis 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…And as result of a multivariate analysis, hypertension appeared as a risk for arterial thrombosis (Table 5). Ruffatti et al reported hypertension as a risk for the first thrombotic event in aPL carriers by retrospective and prospective cohort studies 16,17 . Previous studies with smaller numbers of patients have also shown the association between hypertension and arterial thrombosis 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal is to accurately predict the risk of APS manifestations based on the laboratory detection and evaluation of antiphospholipid antibodies. Until precise characterization of pathogenic aPLs and methods of their detection become available, the clinical significance of aPLs could only be assessed using aPL determinations in the large patient populations [16][17][18][19]. The same applies to the relative clinical significance of different in-house methods and commercially available kits for aPL determination.…”
Section: Introductionmentioning
confidence: 99%
“…Wahl et al (110) suggested that primary prophylaxis with LDA is beneficial in SLE patients, particularly those with aPL. However, not all studies found a protective effect of LDA against first thrombosis (111)(112)(113), and it is important to note that the only randomized, double-blind, placebo-controlled trial investigating the role of LDA in persistently aPL-positive patients (~60% SLE) with no history of thrombosis demonstrated that LDA is not superior to placebo (111).…”
Section: First Thrombosis Preventionmentioning
confidence: 99%